Algebra

(a+b)(a+b) = a + 2ab + b

2                             2

(a-b)(a-b) = a - 2ab + b

2                            2

(a-b)(a+b) = a - b

2       2

d = rt  (distance) = (rate)*(time)

If x + bx + c = (x + r)(x + s) , 

2

Then r + s = b and rs = c.

The roots of a quadratic are the values of x that make the equation equal to 0.

If ax + bx + c = 0, then:

                               sum of the roots = - 

                         product of the roots =

__

b

a

__

c

a

If x + bx + c = (x + r)(x + s)

2

Then r + s = b and rs = c.